PEDAGOGICAL AND PSYCHOLOGICAL FACTORS OF DEVELOPMENT OF IMMUNITY AGAINST HARMFUL HABITS IN HIGH SCHOOL STUDENTS - Abdulazizova Nilufar Abdurakhmonovna (Journal of Higher Education and Academic Advancement, 2024)
In this article, students daily activities, students' routines and the culture of using mobile devices, prevention of harmful habits in students, ways to get rid of stress, and meaningful organization of students' free time are described in this article